Computers helping people with special needs. 15th International Conference, ICCHP 2016, Linz, Austria, July 13-15, 2016, proceedings /: 15th International Conference, ICCHP 2016, Linz, Austria, July 13-15, 2016, proceedings. Part I : ([2016]) - Unknown
No abstract available